Best of Delectable Foods and Dishes from al-Andalus and al-Maghrib: A Cookbook by Thirteenth-Century Andalusi Scholar Ibn Razīn al-Tujībī (1227-1293) : English Translation with Introduction and Glossary - Nasrallah, Nawal (Islamic History and Civilization, 2021)
The thirteenth-century cookbook Fiḍālat al-khiwān fī ṭayyibāt al-ṭaʿām wa-l-alwān by the Andalusi scholar Ibn Razīn al-Tujībī showcases the sophisticated cuisine that developed in the Iberian Peninsula under Muslim rule through its 475 exquisite recipes. Now available for the first time in English, this edition contains al-Tujībī's complete text, based on a newly discovered manuscript now available for the first time in any language. To introduce readers to the wonders of cooking and foodways in al-Andalus and the Maghreb, the translated text is supplemented with an extensive introduction and glossary, illustrated throughout with 218 color miniatures and artifacts, with 24 modernized recipes to give readers a taste of the cuisine. This is a key resource on medieval material culture and the Arab culinary heritage in Iberia, and a delight to all lovers of food and cookbooks.